Inhibition Peroxiredoxin‐2 by Capsaicin Ameliorates Rheumatoid Arthritis via ROS‐Mediated Apoptosis in Fibroblast‐Like Synoviocytes - He, Hengkai; Hao, Mingjing; Luo, Piao; Chen, Junhui; An, Yehai; Huang, Jingnan; He, Ruiyi; Du, Qingfeng; Zhang, Qian; Wang, Jigang (MedComm (2020), 2025)
ABSTRACT Rheumatoid arthritis (RA), a prevalent and incurable autoimmune disease globally, is characterized by the immune system attacking the body's own tissues, leading to joint inflammation and damage. Capsaicin (CAP), from Capsicum annuum L., is known for its burning sensation‐inducing property and has shown various pharmacological effects, yet its specific mechanisms and targets in RA treatment remain largely unclear. This study aimed to investigate the role of CAP in RA by synthesizing CAP probes and using activity‐based protein profiling. We found that CAP reduced joint swelling in arthritic mice and exerted anti‐inflammatory and antiproliferative effects on fibroblast‐like synoviocytes. We identified that CAP binds to PRDX2, inhibiting its antioxidant function and inducing oxidative stress and apoptosis, contributing to the antiarthritic effects. These results suggest that PRDX2 is a potential target for CAP in RA treatment, providing new insights into the molecular mechanisms and potential therapeutic strategies for RA. Capsaicin attenuating arthritis by inhibiting AKT phosphorylation and activating the NRF2–HO‐1 axis via targeting PRDX2